Effect of Emissary Vein on Hemodynamics of the Transverse- Sigmoid Sinus Junction - Qiu, Xiaoyu; Zhao, Pengfei; Li, Xiaoshuai; Ding, Heyu; Lv, Han; Mu, Zhenxia; Xue, Xiaofei; Gong, Shusheng; Yang, Zhenghan; Gao, Bin; Wang, Zhenchang (Frontiers in Human Neuroscience, 2021)
Objective: To investigate the effect of the blood flow direction and afflux location of emissary veins (EVs) on the hemodynamics of the transverse-sigmoid sinus (TS-SS) junction. Methods: A patient-specific geometric model was constructed using computed tomography venography and 4D flow MR data from a venous pulsatile tinnitus (PT) patient. New EV models were assembled with the afflux at the superior, middle and inferior portions of the SS from the original model, and inlet and outlet directions were applied. Computational fluid dynamics simulation was performed to analyze the wall pressure and flow pattern of the TS-SS junction in each condition. Results: Compared to the model without EVs, the wall pressure was greatly increased in models with inlet flow and greatly decreased in models with outlet flow. The more closely the EV approached the TS-SS, the larger the pressure in models with inlet flow, and the smaller the pressure in models with outlet flow. The flow streamline in the lateral part of the TS-SS junction was smooth in all models. The streamlines in the medial part were regular spirals in outlet models and chaotic in inlet models. The streamlines showed no obvious changes regardless of afflux location. The velocity at the TS-SS junction of inlet models were uniform, medium-low flow rate, while in control and outlet models were the lateral high flow rate and the central low flow rate. Conclusion: The flow direction and afflux location of EVs affect the hemodynamics of the TS-SS junction, which may influence the severity of PT.